2021
DOI: 10.1021/acsomega.1c02520
|View full text |Cite
|
Sign up to set email alerts
|

Combustion Kinetics and Mechanism of Pre-Oxidized Coal with Different Oxygen Concentrations

Abstract: The phenomenon of spontaneous combustion of “oxidized coal” is common in mining processes of goafs, thick coal seams, and unsealing of closed fire areas. In order to study the reburning characteristics of coal with different oxidation degrees, the oxygen concentration in the pre-oxidation process was selected as the key influencing factor. Thermogravimetric analysis (TGA) and in situ Fourier-transform infrared (FT-IR) spectroscopy were used to study the macro- and microcharacteristics of raw and oxidized coal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Domestic and foreign scholars have successively designed many experimental devices for the study of the influencing factors of coal spontaneous combustion. Fan et al 1 studied the macro and micro characteristics of raw coal and oxidized coal in the combustion stage by thermogravimetric analysis and in situ Fourier transform infrared spectroscopy. The results show that preoxidation treatment can promote and inhibit the weight loss characteristics of oxidized coal.…”
Section: Introductionmentioning
confidence: 99%
“…Domestic and foreign scholars have successively designed many experimental devices for the study of the influencing factors of coal spontaneous combustion. Fan et al 1 studied the macro and micro characteristics of raw coal and oxidized coal in the combustion stage by thermogravimetric analysis and in situ Fourier transform infrared spectroscopy. The results show that preoxidation treatment can promote and inhibit the weight loss characteristics of oxidized coal.…”
Section: Introductionmentioning
confidence: 99%
“…Coal spontaneous combustion is a highly compound procedure. The characteristics of coal spontaneous combustion are mainly studied from two scales: micro and macro (Wang et al 2021;Deng et al 2018;Fan et al 2021). The particle size is one of the main external factors affecting coal spontaneous combustion (Zhang et al 2019;Yi et al 2014a;Yi et al 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of oxygen concentration, Zhong et al [6][7][8] analyzed the low-temperature oxidation kinetic properties of pre-oxidized coal at various concentrations of oxygen using TG-DSC and found that the differences in kinetic parameters at different oxygen concentrations were very small. Qi et al 9 used thermodynamic methods to analyze the oxidizing characteristics of pre-oxidized coal under a low-oxygen atmosphere in a targeted manner.…”
mentioning
confidence: 99%